Impact of Distributed Rooftop Photovoltaic Systems on Short-Circuit Faults in the Supplying Low Voltage Networks - Hosseinian Yengejeh, H.; Shahnia, F.; Islam, Syed (Taylor & Francis, 2017)
Â© 2017, Copyright Â© Taylor & Francis Group, LLC. This article evaluates the effect of randomly distributed, residential single-phase rooftop photovoltaic systems in the low voltage residential networks, during short-circuit faults on the overhead lines. The important parameters such as the fault current, the current sensed at the distribution transformer secondary, and the voltage profile along the feeder during the fault are examined. A sensitivity analysis is carried out in which the rating and location of the photovoltaic systems in the feeder, as well as the fault location and type, are the considered variables. Moreover, to demonstrate the effect of multiple photovoltaic systems with different ratings and penetration levels when distributed unequally among three phases of the network, a stochastic analysis is carried out. The article summarizes the outcomes of these two analyses to provide a better understanding of the impact of single-phase rooftop photovoltaic systems on the residential feeders during short-circuit faults.